Evolution of functional mitral regurgitation and left atrial function in patients receiving cardiac resynchronization therapy. (3rd October 2022) - Stassen, J; Galloo, X; Hirasawa, K; Van Der Bijl, P; Marsan, N A; Bax, J J
Abstract: Background: Left atrial (LA) function is a strong prognostic marker in patients with heart failure and patients with functional mitral regurgitation (MR). Although cardiac resynchronization therapy (CRT) has shown to improve MR severity, the interaction between a reduction in MR severity and an improvement in LA function, as well as their association with outcomes, has not been investigated. Purpose: To investigate the association between a reduction in MR severity and an improvement in LA function, as well as their association with outcomes. Methods: LA reservoir strain (RS) was evaluated with speckle tracking echocardiography in patients with moderate and severe functional MR. MR improvement was defined as at least 1 grade improvement in MR severity at 6 months after CRT implantation. The association between MR improvement and change in LARS was evaluated using multivariable logistic regression analysis. Patients were dividing into 3 groups: MR non-improvers; MR improvers with no LARS improvement; and MR improvers with LARS improvement. The primary endpoint was all-cause mortality. Results: A total of 340 patients (mean age 66±10 years, 73% male) were included, of whom 200 (59%) showed MR improvement after CRT implantation. On multivariable analysis, an improvement in MR was independently associated with an improvement in LARS (OR 1.008; 95% CI 1.003–1.013; p=0.002) (Table 1). MR improvers showing LARS improvement had the lowest mortality rate, whereas outcomes were not significantly different between MR non-improvers and MR improvers showing no LARS improvement (p=0.236) (Figure 1). Conclusion: In patients with HF and significant functional MR, an improvement in MR after CRT implantation is independently associated with an improvement in LARS, which in turn, is associated with better survival. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): ESC Training Grant App000064741